تطبيق الطريقة المباشرة لترقية مهارة الإستماع و الكلام لتلاميذ الصف العاشر بالمدرسة العالية الحكومية ١ ممباوة - Humam, Ihsan; Rahmap, Rahmap; Arifudin, Arifudin (Armala, 2023)
This study aims to: 1) Know the listening and speaking skills in learning Arabic for students of class X IPA MAN 1 Mempawah before using the Direct Method. 2) Know the steps for applying the Direct Method in learning Arabic to improve listening and speaking skills in class X IPA MAN 1 Mempawah. 3) Knowing the improvement of listening and speaking skills in learning Arabic after applying the Direct Method. This type of qualitative research using the case study method. The population is all students of MAN 1 Mempawah from all majors as many as 136 students and the sample in this study was taken using Simple random sampling, namely a random sampling technique from all populations, namely all students in class X IPA totaling 40. The research instrument was observation, documentation and interviews. The data analysis technique used is descriptive analysis. The results showed that: 1) students' skills in listening and speaking Arabic before the direct method was applied did not have an active response from students with no response when the teacher asked about learning Arabic using Arabic. The class atmosphere became silent, no students answered the teacher's questions because they used Arabic. 2) students' skills are improved by using the direct method in learning Arabic using steps in the form of: providing motivation in Arabic at the beginning of learning in the form of singing Arabic songs (early stage), during learning Arabic the researcher explains learning according to the theme with the style of the language used new to using body movements and actions that are directly visible to students, observing students with attention to the activeness of students in receiving learning, conducting and determining students who are active with direct methods in Arabic so that it is possible to find student results in listen and speak Arabic using the direct method. 3) students' listening and speaking Arabic skills after being applied the direct method have a positive effect with changes in the classroom atmosphere and students' activeness in speaking Arabic through oral questions from researchers from the start of learning researchers and students speak Arabic to each other but not always speak Arabic because there is still a lack of student vocabulary outside of learning. With this stated that the application of the direct method can improve students' listening and speaking Arabic skills.